Upwelling characteristics in the Gulf of Riga (Baltic Sea): multiple data source approach - Skudra, Māris; Väli, Germo; Ikauniece, Anda; Papirtis, Miks (Frontiers in Marine Science, 2023)
Upwellings are characteristic for the Baltic Sea region including the Gulf of Riga, although the current knowledge is rather limited with only few research conducted in the Gulf itself. Upwelling events in the Gulf of Riga in 2010–2022 were studied by analyzing sea surface temperature time series from coastal stations and SmartBuoy, together with satellite data, model data, and CTD (conductivity, temperature, and depth) surveys. The starting/end point, active, and relaxation phases were defined in each event to describe the characteristics and length of each phase. Upwellings were less frequent (41%) on the eastern coast but lasted longer and had higher temperature drops than on the western coast. On the western coast, a variety of upwelling characteristics between stations only 30 km apart were found with the likely reason being the different orientations of the coastline with respect to the wind direction. Satellite data revealed that on the western coast of the Gulf, rather small upwelling events form along specific sections of the coastline. Of all upwelling events, 30% were characterized by an immediate temperature increase after reaching the minimum temperature, and we suggest that this is related to a distinct change in wind direction. The results from the simulations indicated smaller lateral density and salinity gradients in the sea surface than in larger Baltic Sea gulfs. It signals that conditions for the occurrence of baroclinic instabilities are rather small; thus, we suggest that weaker gradients could explain quite fast upwelling relaxation in the basin if compared to, e.g., the Gulf of Finland.